Efficient Organic Dye‐Sensitized Solar Cells: Molecular Engineering of Donor–Acceptor–Acceptor cationic dyes. Issue 12 (13th September 2013) - Cheng, Ming; Yang, Xichuan; Zhao, Jianghua; Chen, Cheng; Tan, Qin; Zhang, Fuguo; Sun, Licheng
Abstract Three metal‐free donor–acceptor–acceptor sensitizers with ionized pyridine and a reference dye were synthesized, and a detailed investigation of the relationship between the dye structure and the photophysical and photoelectrochemical properties and the performance of dye‐sensitized solar cells (DSSCs) is described. The ionization of pyridine results in a red shift of the absorption spectrum in comparison to that of the reference dye. This is mainly attributable to the ionization of pyridine increasing the electron‐withdrawing ability of the total acceptor part. Incorporation of the strong electron‐withdrawing units of pyridinium and cyano acrylic acid gives rise to optimized energy levels, resulting in a large response range of wavelengths. When attached to TiO2 film, the conduction band of TiO2 is negatively shifted to a different extent depending on the dye. This is attributed to the electron recombination rate between the TiO2 film and the electrolyte being efficiently suppressed by the introduction of long alkyl chains and thiophene units. DSSCs assembled using these dyes show efficiencies as high as 8.8 %.